2020
DOI: 10.3390/cancers12123655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Total Neoadjuvant Therapy vs. Standard Chemoradiotherapy in Locally Advanced Rectal Cancer: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Multimodality treatment is a standard of care for LARC, but the optimal sequencing of the treatment modalities remains unclear. Several randomized clinical trials (RCTs) compared total neoadjuvant treatment (TNT) vs. standard neoadjuvant chemoradiotherapy (CRT) with inconsistent results. A systematic review and meta-analysis was performed to evaluate the efficacy of TNT in terms of complete pathological response (pCR) rate, disease-free and overall survival vs. standard CRT in LARC. A systematic search was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…A series of studies supported the application of TNT due to improved long-term survival outcomes, especially the recently published multicenter RCTs (RAPIDO 21 and PRODIGE 20 trial) further con rmed the survival bene ts of TNT. A recent systemic review and meta-analysis included eight RCTs had a conclusion that TNT could signi cantly improve OS and DFS of locally advanced rectal cancer, compared to NCRT 44 . Similar to this meta-analysis, our study included not only RCTs, but also non-RCTs, the nal results also revealed that TNT had the potential of improving long-term survival outcomes of locally advanced rectal cancer patients, both the RCTs and non-RCTs supported the superiority of TNT.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies supported the application of TNT due to improved long-term survival outcomes, especially the recently published multicenter RCTs (RAPIDO 21 and PRODIGE 20 trial) further con rmed the survival bene ts of TNT. A recent systemic review and meta-analysis included eight RCTs had a conclusion that TNT could signi cantly improve OS and DFS of locally advanced rectal cancer, compared to NCRT 44 . Similar to this meta-analysis, our study included not only RCTs, but also non-RCTs, the nal results also revealed that TNT had the potential of improving long-term survival outcomes of locally advanced rectal cancer patients, both the RCTs and non-RCTs supported the superiority of TNT.…”
Section: Discussionmentioning
confidence: 99%
“…Because the pathological response status has a positive effect on disease-free survival (DFS) ( 24 ), the 41-GPS should be used to predict the survival benefit of 5-FU-based nCRT. First, we used the signature to evaluate the survival benefit of 105 patients with rectal cancer treated with 5-FU-based nCRT in the GSE87211 cohort.…”
Section: Methodsmentioning
confidence: 99%
“…In a review of ERUS/MRI staged patients with mid-and distal rectal clinical T3N0 tumours, detection of mesorectal lymph node positivity in resected specimens was 22% despite neoadjuvant CRT [18]. for DFS, hazard ratio [HR] = 0.82, 95% CI 0.71-0.95, P = 0.01 and OS, HR = 0.81, P = 0.04) without significant increase in serious adverse reactions [19]. However, this meta-analysis did not include the updated long term follow-up data from the Polish II trial which revealed no significant OS advantage with short course RT followed by chemotherapy versus conventional CRTA.…”
Section: Cu R R E Nt S Tatusmentioning
confidence: 99%
“…However, neither the PRODIGE nor RAPIDO trial has demonstrated an overall survival advantage [1–4]. A meta‐analysis including 8 randomized controlled trials and 2301 patients has also indicated an improvement in pCR rates in addition to DFS and OS at 3 years compared to standard neoadjuvant chemoradiotherapy (for pCR, odds ratio [OR] = 1.99, 95% confidence interval [CI] 1.59–2.49, P < 0.001; for DFS, hazard ratio [HR] = 0.82, 95% CI 0.71–0.95, P = 0.01 and OS, HR = 0.81, P = 0.04) without significant increase in serious adverse reactions [19]. However, this meta‐analysis did not include the updated long term follow‐up data from the Polish II trial which revealed no significant OS advantage with short course RT followed by chemotherapy versus conventional CRTA.…”
Section: Current Statusmentioning
confidence: 99%